Pengaruh Media Tanam Tanah Pasca Tambang dan Panjang Buku Terhadap Pertumbuhan Stek Tanaman Lada (Piper nigrum L.) Varietas Malonan I - Ferdy Hidayat; Mahdalena Mahdalena; Winda Isdianti (Universitas Widya Gama Mahakam, 2019)
The Effect of Post-Mining Soil Planting Media and Book Lengths on the Growth of Pepper Cutters (Piper nigrum L.) Varieties of Malonan I, Under the guidance of Mahdalena and Iin Arsensi. The purpose of this study was to determine the response of the growth of pepper cuttings (Piper nigrum L.) Malonan I variety using post-mining soil planting media. This research was carried out in Sungai Mariam Village, Anggana Subdistrict for 6 weeks from September to November 2018. The research was arranged in a Randomized Block Design (RBD) with Factorial experiments consisting of 2 factors with 3 replications. The first factor is the length of the book consists of two levels, namely s1 (length 3 books) and s2 (length 5 books). The second factor of the growing media consists of 3 levels, namely t1 (mining land), t2 (mining land and manure), and t3 (mining land and compost). The results showed that the treatment of post-mining soil planting media and the length of cuttings did not have a significant effect on all parameters, when growing shoots, number of shoots, and shoot length were 2, 4, 6 weeks after planting.